(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A new Celtiberian tessera, which seems to come from Ciadueña (Soria), is presented. The circumstances of the finding and the Ciadueña archaeological site are exposed. Afterwards the tessera is described and its formal parallels are brought into discussion. An interpretation and translation are advanced along whit the pros and cons of the consideration of the piece as authentic.